2021
DOI: 10.1101/2021.03.03.433597
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maturation signatures of conventional dendritic cell subtypes in COVID-19 reflect direct viral sensing

Abstract: Growing evidence suggests that conventional dendritic cells (cDCs) undergo aberrant maturation in COVID-19, and this adversely affects T cell activation. Here, we find that cDC2 subtypes show similar infection-induced gene signatures with an increasing gradient of expression of interferon-stimulated genes from mild to severe patients and a down-regulation of major histocompatibility complex class II (MHC class II) molecules and some inflammatory cytokines compared to the baseline level of healthy donors. In vi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…The former serve as potent antigen- presenting cells (APCs), while the latter is a specialized subset that can produce type 1 IFN ( 60 , 61 ). It has been found that pDC along with viral sensing, interferon signaling and antigen presentation are more defective in severe versus mild COVID-19 ( 62 68 ). Further impairment in DC maturation and function in severe vs. mild disease may be associated with a worse disease ( 69 ).…”
Section: The Relationship Between the Innate Immune System And The Pr...mentioning
confidence: 99%
“…The former serve as potent antigen- presenting cells (APCs), while the latter is a specialized subset that can produce type 1 IFN ( 60 , 61 ). It has been found that pDC along with viral sensing, interferon signaling and antigen presentation are more defective in severe versus mild COVID-19 ( 62 68 ). Further impairment in DC maturation and function in severe vs. mild disease may be associated with a worse disease ( 69 ).…”
Section: The Relationship Between the Innate Immune System And The Pr...mentioning
confidence: 99%
“…Severe COVID-19 is characterized by increased cell death: the elevated levels of interferon (IFN)-γ and TNF that are observed in patients with severe disease induce a form of cell death called PANoptosis [ 23 ], which initiates a feed-back loop that sustains lymphopenia, tissue damage, and inflammation. Another key feature of the immunosuppressive phase of sepsis is decreased antigen presentation – this is also a hallmark of severe COVID-19, that is characterized by HLA-DR lo circulating monocytes and dendritic cells [ 24 , 25 , 26 ]. In addition, the gene signatures of monocytes derived from patients with severe sepsis and from those with severe COVID-19 are strikingly similar [ 15 ].…”
Section: Covid-19 Is An Inflammatory Disordermentioning
confidence: 99%
“…Dendritic cells as professional antigen-presenting cells (APCs) are central players in the initiation of adaptive responses, leading to elimination of viral infections [52] . Analysis of conventional dendritic cells (cDCs) in severe and mild COVID-19 patients illustrated decreased expression of co-stimulatory proteins, MHCII, and TAP molecules and increased levels of pro-inflammatory molecules including complement and coagulation factors in severely ill patients [53] . Moreover, plasmacytoid dendritic cells (pDCs) are known as IFN producers in the innate immune system.…”
Section: Immunoediting In Sars-cov-2mentioning
confidence: 99%